MENANGANI PENYAKIT DEMAM BERDARAH DENGAN ALGORITMA RETE DAN CERTAINTY FACTOR (Studi Kasus: Puskesmas Umbulharjo II Yogyakarta) - Sahal, Ahmad; Hartati, Sri (Universitas Respati Yogyakarta, 2013)
In meeting the needs of health care that supports prevention and early detection of Dengue Hemorrhagic Fever (DHF), the existing health centers always keep their respective areas. In health centers that handle DBD mostly nurses in nursing care. To improve the service to the community as well as the lack of specialists in health center required an expert system, are used as a tool of nursing care in diagnosing dengue disease.JESS (Java Expert System Shell) is an expert system shell for Java, using the Rete algorithm as well as forward-chaining search and characterization of the disease using a confidence level of certainty factor (CF), it can be made in favor of the establishment of a knowledge base of expert system. The process for making the diagnosis is done by examining the clinical symptoms and laboratory disease. The diagnosis comes with a confidence level (percentage) of her illness by patients with DHF.From the test results were obtained from 10 cases of medical records of data centers Umbulharjo II Yogyakarta, the percentage obtained by 100% the truth value of predictive diagnostics system according to the knowledge possessed by experts.Â Â Keywords: JESS, Rete, Certainty Factor, Nursing Care, Expert System